A Sociological Analysis of Nepalese Banking: Historical Perspective - Gartaula, Milan Raj (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
In the context of Nepal, banking is basically understood to provide loan and accept deposit centering on interest. So, banking and interest are two inseparable parts. This article aims to view banking and interest from a sociological perspective. There are many sociological explanations about banking practices but they have not been adequately documented and analyzed, especially in the context of Nepal. This is the statement of the problem. Even those documents that do exist provide only provide indirect explanations on the matter. Is interest system solely economic or do there exist other non-economic factors as well? This is the research question here. This article aims to find out how sociological aspects like gender, religion, caste and special age group influence banking and interest. And finally this article finds out that interest system is uniquely tied to the aforementioned sociological aspects.